The effect of working from home (WFH) during MCO on work productivity - Roslinah Mahmud; Beatrice Lim Fui Yee; Khairul Hanim Pazim; Noor Faziedah Chun Lee; Kasim Mansur (Universiti Malaysia Sabah, 2020)
COVID-19 has led to dramatic changes like work and how work can be performed. Among various options, a flexible work arrangement allows workers to work from home (WFH) as a form of work continuity in times of crisis. To curb Covid-19 in Malaysia, the Government imposed Movement Control Order from 18 March 2020. The Movement Control Order has halted all non-essential economic activities in the country. The restrictions also forced the temporary closure of schools, higher education institutions (HEIs) and all government and private premises. Overnight, workers were forced to work from home. The main objective of this study is to investigate the effects and factors of WFH on employees’ productivity during the crisis. Based on the literature review, there is a positive effect WFH towards employees’ productivity and the factors that influence the relationship are demographics, the nature of the work, and technology. The findings will add to the limited literature on the impact of WFH on work productivity and work-life balance.